2011
DOI: 10.2460/ajvr.72.10.1305
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and physiologic effects of intramuscularly administered xylazine hydrochloride-ketamine hydrochloride-butorphanol tartrate alone or in combination with orally administered sodium salicylate on biomarkers of pain in Holstein calves following castration and dehorning

Abstract: SAL administered PO through drinking water decreased cortisol concentrations and reduced the decrease in ADG associated with castration and dehorning in calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 49 publications
7
41
0
Order By: Relevance
“…Our investigation of chute exit velocity suggests that, in acclimated Holstein calves, the measure may be indicative of a difference in type or area of pain perception but did not indicate that a painful procedure increased the desire or ability to move away from the chute faster than control calves. Although as reported in Baldridge et al (2011) chute exit velocity is not useful in sedated calves, the measure might be a useful adjunct in assessing nonsedating methods of pain relief due to castration but not dehorning. Surgical castration is generally followed by a period of reduced BW gain, the severity of which is usually related to the age of the animal at the time of the procedure (Bretschneider, 2005;Stafford and Mellor, 2005b;AVMA, 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our investigation of chute exit velocity suggests that, in acclimated Holstein calves, the measure may be indicative of a difference in type or area of pain perception but did not indicate that a painful procedure increased the desire or ability to move away from the chute faster than control calves. Although as reported in Baldridge et al (2011) chute exit velocity is not useful in sedated calves, the measure might be a useful adjunct in assessing nonsedating methods of pain relief due to castration but not dehorning. Surgical castration is generally followed by a period of reduced BW gain, the severity of which is usually related to the age of the animal at the time of the procedure (Bretschneider, 2005;Stafford and Mellor, 2005b;AVMA, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 2-to 4-mo-old Holstein calves, Baldridge et al (2011) reported no net ADG over a period of 13 d after a concurrent castration and dehorning procedure. This result is similar to that observed after the same procedure (CD 1 ) in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the NSAID sodium salicylate administered in drinking water for 2 d after dehorning and castration reduced serum cortisol after surgery and improved ADG over 13 d (Baldridge et al, 2011). Meloxicam is an NSAID that is approved in Canada for pain relief after disbudding in calves.…”
Section: Introductionmentioning
confidence: 99%